One Student’s English Language Learning Experience: The Story of a Non-English Major College Student in Indonesia - Asri Siti Fatimah; Fuad Abdullah; Jember Barkah Abdillah Adiprima (Indonesian TESOL Journal, 2023)
English plays an indispensable role in fostering academic, personal, and professional quality. In Indonesia, introducing English to students from elementary, secondary, and tertiary levels of education is highly demanding. Unfortunately, probing the non-major English student's learning experiences remains under-researched. Therefore, this study is aimed at scrutinising the English language learning experience of a non-English major college student in Indonesia. John (pseudonym), a talented and outstanding student from the non-English major of a state university in Tasikmalaya, West Java, was recruited as the investigative participant. The data were garnered through semi-structured interviews and analysed using Narrative Analysis (NA) (Labov & Waletsky, 1967). The findings reveal that supporting environment, learning motivation, and styles have become the most influential aspects for him to learn English. With this in mind, encouraging John to acquire Basic Interpersonal Communication Skills (BICS) and Cognitive Academic Language Proficiency (CALP) enables him to communicate in English successfully. Further, this study suggests that English is not only taught for classroom-oriented activities but also for real-life communicative purposes.  Keywords: Language Learning Experience; Narrative Inquiry; Non-major English Student